Budd-Chiari syndrome and its associated hepatocellular carcinoma: Clinical risk factors and potential immunotherapeutic benefit analysis - Li, Kang-Shuai; Guo, Sen; Chen, Yu-Xin; Zhang, Zong-Li (Frontiers in Oncology, 2022)
Background Hepatocellular carcinoma (HCC) is a well-described complication of Budd-Chiari syndrome (BCS). However, the risk factors of BCS in developing HCC and clinical characteristics and imaging features of BCS-associated HCC is still to be determined. Methods Data from 113 consecutive patients with primary BCS in Qilu hospital were retrospectively studied. The clinical features of 12 HCC patients associated with BCS were also analyzed. Chi-square analysis was performed to analyze the differences in clinical characteristics. The treatment regime and CT imaging features of BCS-associated HCC were also illustrated. Results 113 consecutive patients admitted to our hospital between January 2009 and June 2016 with a primary diagnosis of BCS were enrolled. 10.6% (12/113) was diagnosed with HCC. The BCS patients were mainly male gender with an average age of 49.2 years. Symptom duration longer than one year exhibited decreased serum ALT and AST and increased ascites ratio. BCS-associated HCC patients were presented with IVC block and stricture of the hepatic venous outflow tract. Patients with HCC were older and showed elevated serum AST and total bilirubin. Most nodules of HCC located in the right posterior lobe with heterogeneous enhancement during the arterial phase and washout during the delayed phase. Conclusions The results indicate that BCS patients with IVC block and stricture of hepatic venous outflow tract seem to be associated with HCC. BCS associated HCC nodules exhibited irregular and heterogeneous enhancement in the arterial phase and washout on the delayed phase.